The Effect of Islamic Social Reporting (ISR) and Corporate Zakat Disclosure on the Profitability of Sharia Commercial Banks in Indonesia in 2019-2024 - Mauliana, Tria; Madnasir, Madnasir; Syarif , Ahmad Hazas (Neo Journal of economy and social humanities, 2026)
This study aims to analyze the impact of Islamic Social Reporting (ISR) and corporate zakat disclosure on the profitability of Islamic Commercial Banks in Indonesia from 2019 to 2024. This study adopts a quantitative approach with a causal associative research type. The data used is secondary data obtained from the annual reports and sustainability reports of Islamic Commercial Banks registered with the Financial services Authority (OJK). The sampling technique was carried out using purposive sampling, resulting in 6 banks with a total of 36 observations. The research findings indicate that ISR has a negative and significant impact on profitability as measured by Return on Assets (ROA). Corporate zakat disclosure also shows a negative and significant impact on profitability. However, at the same time, ISR and corporate zakat disclosure have a significant effect on the profitability of Islamic Commercial Banks. These findings indicate that sharia-based social reporting practices and zakat transparency are important factors in supporting the accountability of Islamic financial institutions, even though in the short term they can put pressure on financial performance.